2008
DOI: 10.1016/j.pedn.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Perinatal Steroids: Child Development of Preterm Infants

Abstract: The development of premature infants may be altered due to exposure to high cumulative doses of the perinatal corticosteroid dexamethasone during critical growth periods. To compare child behavioral development of prematurely born infants who were exposed to higher perinatal steroids (PNS; N0.2 mg/kg) with that of infants exposed to lower PNS (≤0.2 mg/kg), we used the Vineland Adaptive Behavioral Scales to assess school-age behavioral outcomes of a historical cohort of 45 prematurely born infants. Children who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
4
0
4
Order By: Relevance
“…Moreover, prenatal GCs can disrupt the function of the hypothalamus-pituitary-adrenal (HPA) axis and thus permanently alter the stress response of the offspring (Huang, 2011). Likewise, clinical follow-up studies of children and adults exposed perinatally to high levels of GCs, reported cognitive and behavioral abnormalities (Lupien et al, 2009; McEwen, 2005; Purdy et al, 2008; Reynolds and Seckl, 2012; Welberg and Seckl, 2001). Furthermore, there are numerous reports linking high levels of GCs in utero with cognitive abnormalities and even increased probability of developing schizophrenia (Bombin et al, 2012; Huang, 2011; Lupien et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prenatal GCs can disrupt the function of the hypothalamus-pituitary-adrenal (HPA) axis and thus permanently alter the stress response of the offspring (Huang, 2011). Likewise, clinical follow-up studies of children and adults exposed perinatally to high levels of GCs, reported cognitive and behavioral abnormalities (Lupien et al, 2009; McEwen, 2005; Purdy et al, 2008; Reynolds and Seckl, 2012; Welberg and Seckl, 2001). Furthermore, there are numerous reports linking high levels of GCs in utero with cognitive abnormalities and even increased probability of developing schizophrenia (Bombin et al, 2012; Huang, 2011; Lupien et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly developmental assessment of the interplay between behavioral problems and motor, cognitive, and/or language skills is valuable to this research. In the present study, we examined developmental scores from our prior research with the Vineland Adaptive Behavioral Scales in our current regressions (see Table 5) and found no statistically significant associations (Purdy et al, 2008; Sparrow, Balla, & Cicchetti, 1984). …”
Section: Discussionmentioning
confidence: 80%
“…Regression for Internalizing Problems scale: R 2 = .51, Δ R 2 = .42; for Total Competence scale: R 2 = .84, Δ R 2 = .73); and for Total Problems scale: R 2 = .950, Δ R 2 = .92. CRIB = Clinical Risk Index for Babies; NICU = neonatal intensive care unit; PNS = perinatal steroid; VABS = Vineland Adaptive Behavior scales. a VABS data from prior study (Purdy, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…A partir desta configuração, a subcategoria 1c destacouse das demais, indicando que 50% (f = 24) dos estudos realizaram o follow-up de prematuros entre o nascimento e a adolescência (Berbis et al, 2012;Bohm & Katz-Salamon, 2003;Brown et al, 2014;Caravale et al, 2012;Charkaluk et al, 2012;Claas et al, 2011;Cooke, 2006;Doyle et al, 2012;Feldman, 2009;Gurka et al, 2010;Halbwachs et al, 2014;Jongmans et al, 1993;Korja et al, 2014;Leppänen et al, 2014;Leversen et al, 2012;Lind et al, 2010;Luu et al, 2011;Munck et al, 2012;Nepomnyaschy et al, 2012;Purdy et al, 2008;Rodriguez et al, 2011;Schothorst et al, 2007;Schepers et al, 2012;Treyvaud et al, 2013). A seguir, tem-se a subcategoria 1a, na qual 27,08% (f = 13) dos artigos avaliaram os prematuros entre o nascimento e os 36 meses de vida (Fraga et al, 2008;Gabis et al, 2015;Houtzager et al, 2010;Katz-Salamon et al, 2000;Khan et al, 2008;Newnham et al, 2009;Petit et al, 2016;Pineda et al, 2014;Pinto, 2009;Poggioli et al, 2016;Ross et al, 2016;Stolt et al, 2014;Voigt et al, 2013).…”
Section: Resultsunclassified
“…A subcategoria 2g, que objetivou avaliar o comportamento, a autorregulação e a afetividade de crianças prematuras, abrangeu 14% (f = 7) dos estudos (Feldman, 2009;Gurka et al, 2010;Houtzager et al, 2010;Korja et al, 2014;Pinto, 2009;Purdy et al, 2008;Voigt et al, 2013). Há ainda a subcategoria 2h, que buscou a prevalência de transtornos psiquiátricos e problemas emocionais, constituindo 8% (f = 4) dos artigos selecionados (Nomura et al, 2007;Rodriguez et al, 2011;Schothorst et al, 2007;Treyvaud et al, 2013).…”
Section: Resultsunclassified